Alginate-based aerogels as wound dressings for efficient bacterial capture and enhanced antibacterial photodynamic therapy. (31st December 2022) - Guo, Ning; Xia, Yu; Zeng, Weishen; Chen, Jia; Wu, Quanxin; Shi, Yaxin; Li, Guoying; Huang, Zhuoyi; Wang, Guanhai; Liu, Yun
Abstract: The development of novel wound dressings, such as aerogels, with rapid hemostasis and bactericidal capacities for pre-hospital care is necessary. To prevent the occurrence of bacterial resistance, antibacterial photodynamic therapy (aPDT) with broad-spectrum antibacterial ability and negligible bacterial resistance has been intensively studied. However, photosensitizers often suffer from poor water solubility, short singlet oxygen ( 1 O2 ) half-life and restricted 1 O2 diffusion distance. Herein, sodium alginate was covalently modified by photosensitizers and phenylboronic acid, and cross-linked by Ca(II) ions to generate SA@TPAPP@PBA aerogel after lyophilization as an antibacterial photodynamic wound dressing. Afterwards, its photodynamic and bacterial capture activities were intensively evaluated. Furthermore, its hemostasis and bactericidal efficiency against Staphylococcus aureus were assessed via in vitro and in vivo assays. First, chemical immobilization of photosensitizers led to an enhancement of its solubility. Moreover, it showed an excellent hemostasis capacity. Due to the formation of reversible covalent bonds between phenylboronic acid and diol groups on bacterial cell surface, the aerogel could capture S. aureus tightly and dramatically enhance aPDT. To sum up, the prepared aerogel illustrated excellent hemostasis capacity and antibacterial ability against S. aureus . Therefore, they have great potential to be utilized as wound dressing in clinical trials.